Interpersonal sensitivity in those at clinical high risk for psychosis mediates the association between childhood bullying victimisation and paranoid ideation: A virtual reality study - McDonnell, J.; Stahl, D.; Day, F.; McGuire, P.; Valmaggia, L.R. (Schizophrenia research, 2018)
Experience of bullying victimisation in childhood and heightened interpersonal sensitivity have been independently linked to the clinical high risk for psychosis. To examine the potential mediating effect of interpersonal sensitivity in explaining the link between childhood bullying victimisation and real-time paranoid ideation in adult participants at clinical high risk for psychosis. In a cross-sectional study data were collected for 64 individuals at clinical high risk for psychosis. Measures included history of bullying victimisation, interpersonal sensitivity and state paranoid ideation following exposure to a social virtual reality environment. The virtual reality scenario was a London Underground journey. Path analysis indicated that interpersonal sensitivity fully explained the significant association between severe bullying victimisation in childhood and paranoid ideation in the clinical-high risk group. Based on AIC criteria the best model selected was the full mediation model: severe bullying→interpersonal sensitivity→state paranoid ideation. The results suggest that severity of bullying is more important than frequency of bullying in explaining state paranoid ideation. The significant role played by interpersonal sensitivity in the association between being bullied in childhood and paranoid ideation in the clinical high risk group suggests that this could become a target for intervention.